Kinetic Analysis of [C]Vorozole Binding in the Human Brain with Positron Emission Tomography - Jean Logan; Sung Won Kim; Deborah Pareto; Frank Telang; Gene-Jack Wang; Joanna S. Fowler; Anat Biegon (Molecular Imaging)
Using positron emission tomography, we investigated the kinetics of [ 11 C]vorozole ([ 11 C]VOR), a radiotracer for the enzyme aromatase that catalyzes the last step in estrogen biosynthesis. Six subjects were scanned under baseline conditions followed by retest 2 weeks later. The retest was followed by a blocking study with 2.5 mg of the aromatase inhibitor letrozole. The binding potential (BPA d ) was estimated from a Lassen plot using the total tissue distribution volume ( V T ) for baseline and blocked. BP A ND for the thalamus was found to be 15 times higher than that for the cerebellum. From the letrozole studies, we found that [ 11 C]VOR exhibits a slow binding compartment (small k 4 ) that has a nonspecific and a blockable component. Because of the sensitivity of V T to variations in k 4 , a common value was used for the four highest binding regions. We also considered the tissue uptake to plasma ratio for 60 to 90 minutes as an outcome measure. Using the ratio method, the difference between the highest and lowest was 2.4 compared to 3.5 for the V T . The ratio method underestimates the high regions but is less variable and may be more suitable for patient studies. Because of its kinetics and distribution, this tracer is not a candidate for a bolus infusion or reference tissue methods.